2009
DOI: 10.1101/gad.535209
|View full text |Cite
|
Sign up to set email alerts
|

TBP2 is essential for germ cell development by regulating transcription and chromatin condensation in the oocyte

Abstract: Development of the germline requires consecutive differentiation events. Regulation of these has been associated with germ cell-specific and pluripotency-associated transcription factors, but the role of general transcription factors (GTFs) remains elusive. TATA-binding protein (TBP) is a GTF involved in transcription by all RNA polymerases. During ovarian folliculogenesis in mice the vertebrate-specific member of the TBP family, TBP2/ TRF3, is expressed exclusively in oocytes. To determine TBP2 function in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
98
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 44 publications
9
98
3
Order By: Relevance
“…51,52 A similar phenotype with failure to undergo the secondary follicle-to-antral follicle transition during folliculogenesis is observed in females that lack Taf4b (a germ cell-specific subunit of TFIID), 53 Yy1, 54 or Tbp2 (TATA-binding protein 2). 55 In particular, female mice deficient in the oocyte-specific TBP2 display phenotypes very similar to that observed for Hdac1:2 −/− mice, including infertility, small ovaries, arrest of follicle growth before antrum formation, a decrease in Pol II CTD S2 phosphorylation and histone H3K4 methylation. 55 The similarity in phenotypes suggests that Hdac1 and Hdac2 double mutants and these transcriptional factor mutants share a common mechanism that is linked to a decrease in transcription.…”
Section: Hdac1 and Hdac2 Regulate Oocyte Development Through Transcrimentioning
confidence: 75%
See 1 more Smart Citation
“…51,52 A similar phenotype with failure to undergo the secondary follicle-to-antral follicle transition during folliculogenesis is observed in females that lack Taf4b (a germ cell-specific subunit of TFIID), 53 Yy1, 54 or Tbp2 (TATA-binding protein 2). 55 In particular, female mice deficient in the oocyte-specific TBP2 display phenotypes very similar to that observed for Hdac1:2 −/− mice, including infertility, small ovaries, arrest of follicle growth before antrum formation, a decrease in Pol II CTD S2 phosphorylation and histone H3K4 methylation. 55 The similarity in phenotypes suggests that Hdac1 and Hdac2 double mutants and these transcriptional factor mutants share a common mechanism that is linked to a decrease in transcription.…”
Section: Hdac1 and Hdac2 Regulate Oocyte Development Through Transcrimentioning
confidence: 75%
“…55 In particular, female mice deficient in the oocyte-specific TBP2 display phenotypes very similar to that observed for Hdac1:2 −/− mice, including infertility, small ovaries, arrest of follicle growth before antrum formation, a decrease in Pol II CTD S2 phosphorylation and histone H3K4 methylation. 55 The similarity in phenotypes suggests that Hdac1 and Hdac2 double mutants and these transcriptional factor mutants share a common mechanism that is linked to a decrease in transcription. Indeed, a detailed analysis using mice lacking different combinations of Hdac1 and Hdac2 suggests a threshold level of transcription is required for oocyte development ( Figure 3).…”
Section: Hdac1 and Hdac2 Regulate Oocyte Development Through Transcrimentioning
confidence: 75%
“…As case 1 had a smaller r (X) chromosome compared to case 2, we analysed the additional genes deleted and found that the extra region deleted in case 1 (Xq21.33-Xq22.1) were harbouring genes involved in thyroid hormone signalling, insulin receptor signalling, meiosis regulation, cell cycle regulation and chromatin organization. Alterations in these pathways are reported to be responsible for ovarian dysfunction [1,5,9,31,36,46].…”
Section: Discussionmentioning
confidence: 99%
“…53,56 TRF3 has also been shown to form a complex with TAF3 and play a role in the ex-vivo differentiation of mouse myoblast to myotubes. 57,58 As skeletal muscle differentiation is unaffected in TRF3 knockout mice, 59 the involvement of TRF3 in terminal differentiation in different species awaits further investigation. Importantly, TRF3 of Xenopus and zebrafish is mainly expressed in oocytes and is essential for embryogenesis.…”
Section: Tbp-related Factorsmentioning
confidence: 99%
“…52,54 Mouse TRF3, which is exclusively expressed in oocytes, is essential for the differentiation of female germ cells but not for embryonic development. 59 TRF2 is the TRF protein with the least similarity to TBP. [60][61][62][63][64][65] In 1999-2000, when different research groups have cloned TRF2 from multiple species, different names were coined.…”
Section: Tbp-related Factorsmentioning
confidence: 99%